(untitled) (UCC Student Medical Journal, 2026)
Cultural influences, including language, shared values and social structures, play a critical role in shaping neural organization and brain development. This narrative review from UCC’s Neuroscience and Neurology Society aims to explore new findings in the emerging field of cultural neuroscience, focusing on how an individual’s culture and environment influences their neurocognitive processes, and how this understanding can be applied to advance community-based, inclusive research.